A continental study of Whistling Swans using neck collars - Sladen, William J L (Wildfowl, 1973)
Using coded colour neck collars increased the resighting rate of Whistling Swans Cygnus c. columbianus as individuals to as much as 90%, compared with less than 5% by conventional band methods, even after a migration across N. America. Details of the continental marking protocol for four swan species are given. Much public interest and co-operation has resulted from the use of collars.